2014
DOI: 10.5433/1679-0359.2014v35n6p3205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mesenchymal stem cells on movement and urination of rats with spinal cord injury

Abstract: Cell therapy has frequently been reported as a possible treatment for spinal trauma in humans and animals; however, without pharmacologically curative action on damage from the primary lesion. In this study, we evaluated the effect of administering human adipose-derived stem cells (hADSC) in rats after spinal cord injury. The hADSC were used between the third and fifth passages and a proportion of cells were transduced for screening in vivo after transplantation. Spinal cord injury was induced with a Fogarty c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Motor vehicle accidents (motorcycle, all-terrain vehicle, or automobile) comprised 50% of the SCI etiology (n = 5), followed by fall-related injuries (n = 3), pedestrian-car accidents (n = 1), and surfing accidents (n = 1). The average duration between injury and AD-MSC injection was 11 months (range of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. At the time of injection, five patients were classified as AIS grade A, two as AIS B, and three as AIS C. Patient 9 was injected at 22 months post-injury due to failure of adipose tissue expansion.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor vehicle accidents (motorcycle, all-terrain vehicle, or automobile) comprised 50% of the SCI etiology (n = 5), followed by fall-related injuries (n = 3), pedestrian-car accidents (n = 1), and surfing accidents (n = 1). The average duration between injury and AD-MSC injection was 11 months (range of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. At the time of injection, five patients were classified as AIS grade A, two as AIS B, and three as AIS C. Patient 9 was injected at 22 months post-injury due to failure of adipose tissue expansion.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The use of AD-MSC has been thoroughly investigated in traumatic and degenerative diseases [7][8][9][10][11] . Preclinical trials in SCI animal models have found evidence that AD-MSCs can regulate the inflammatory response and promote a regenerative environment, correlating with promising clinical outcomes [12][13][14][15] .…”
mentioning
confidence: 99%
“…The search came up with 588 non-duplicate results. After initial screening and studying full texts of the articles, 18 articles were included in the current meta-analysis [ 13 16 , 22 35 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the articles presented two different sets of data [ 14 ], so the results from 19 unique experiments were analyzed. Two studies were in Chinese [ 33 , 34 ], and 16 articles were in English [ 13 16 , 22 32 , 35 ]. Experiments were performed on 567 rats (275 rats in the SCI group and 292 rats in ADSCs-treated groups).…”
Section: Resultsmentioning
confidence: 99%
“…A great number of studies have been performed with stem cells from different sources using animal models of spinal cord injury, and even therapeutic attempts on humans, presenting promising results [5][6][7] . However, there are some difficulties to perform a direct comparison of such results, due to the large variability of characterization grade of the transplanted cells, different animal models, and the time fluctuation between injury event and its treatment Commonly, dogs present clinical injuries of the thoracic and lumbar spinal medulla mainly due to herniation or protrusion of the intervertebral discs 9 .…”
mentioning
confidence: 99%